2017
DOI: 10.24200/sci.2017.4312
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behaviour of β-Ti-15333 in Ultrasonically Assisted Turning: Experimental and Numerical Analysis

Abstract: Abstract. The enhanced strength, fatigue life, and corrosion resistance properties of Tialloys have attracted many industries for their utilization in various components exposed to extreme operating conditions. The machining of these alloys using conventional machining techniques is one of the main challenges in its wide application in many components, and there is an obvious demand to analyse the materials' response to these alloys in machining processes by developing simulation-based models. The materials' b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the earlier work of Muhammad et al [19,25], they demonstrated that application of vibration on the cutting insert resulted a decline of 75, 67, and 52% in F x , F y , and F z , respectively. However, in the current work, it was concluded that addition of heat with vibration resulted an additional drop of 15, 11, and 16% in F x , F y , and F z , respectively.…”
Section: Materials Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…In the earlier work of Muhammad et al [19,25], they demonstrated that application of vibration on the cutting insert resulted a decline of 75, 67, and 52% in F x , F y , and F z , respectively. However, in the current work, it was concluded that addition of heat with vibration resulted an additional drop of 15, 11, and 16% in F x , F y , and F z , respectively.…”
Section: Materials Modelmentioning
confidence: 95%
“…The most striking effect reported was the pronounced decline in the levels of observed forces with forced vibrated tool [24,25]. The consequent reduction of chatter and spring-back observed improved dimensional accuracy of the finished components.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The ultrasonic system developed at Loughborough University, UK is an open-loop system and is optimized for the above ultrasonic parameters. The maximum force reduction and improvement in surface nish are reported for Ti-and Ni-based alloys [17,18,22,32]. A four-jaw chuck was used to clamp the workpiece on the lathe machine.…”
Section: Machiningmentioning
confidence: 99%